UJI VIABILITAS BENIH PADA BEBERAPA VARIETAS JAGUNG DENGAN MENGGUNAKAN METODE UJI KERTAS DIGULUNG DIDIRIKAN DALAM PLASTIK (UKDdP) - Gusmeizal Gusmeizal; Dwika Karima Wardani; Angga Ade Sahfitra (KOLONI, 2023)
Corn is the second main food crop after rice which is consumed by Indonesian people. This study aims to examine the germination capacity of corn using the Rolled Paper Test in Plastic (UKDdP) method. The research was conducted at the Laboratory of the Faculty of Agriculture, University of Medan Area in January 2023. The method of analysis in this study used a one-factor Completely Randomized Design consisting of 2 levels, namely corn seeds of the Bonanza F1 variety and corn seeds of the Taste F1 variety. The materials and tools used in this study were corn seeds of the Bonanza F1 variety, corn seeds of the Taste F1 variety, substrate paper, water, plastic, rubber, trays, tweezers, bactericidal and fungicide, analytical scales, calipers, rulers, stationery, microscopes. digital, stationery, and cameras. The observed variables were the percentage of seed germination, plant height, root length, number of roots. The results showed that the percentage of seed germination for the Bonanza F1 variety and the Taste F1 variety reached 100% with the percentage of seeds germinating for the Bonanza F1 variety at 98% and the Taste F1 variety at 85%. Plant height and root length of maize variety Bonanza F1 and maize variety Taste F1 which were tested using the Rolled Paper Test established in Plastic (UKDdP) method had no significant effect. Keywords: Corn Seed, Viability Test, UKDdP